Affected urinary organs at the infiltrative endometriosis - A. I. Ischenko; L. S. Aleksandrov; Yu. V. Chushkov; A. A. Bakhvalova; A. A. Ischenko; L. M. Rappoport; D. G. Tsarichenko; E. A. Bezrukov (Сеченовский вестник)
This article covers the problem of diagnosis and treatment of  urinary organs at the infi ltrative endometriosis.